The effect of seawater and sodium chloride on the compressibility behavior of clay soil - Nurul Asmaa , Ibrahim (2012)
Clayey materials are widely used as a landfills liners and landfill covers due to its low permeability. In some cases, natural soil containing clay minerals are also used. There are number of landfills in Malaysia located near the sea or coastal area such as Pulau Burung Sanitary Landfill and Kota Bharu Municipal Council Landfill. The behaviour of clay liner and their interaction with seawater is not known since the related study is limited in the literature. This study was conducted in order to determine the compressibility behaviour of a natural soil (KB soil) by using seawater and sodium chloride (NaC1) solution. The compressibility behaviour of the soil was obtained by conducting double-oedometer tests. In addition, the effect of seawater and NaCl solution on the physical properties of KB soil also was identified. The results indicated that the pressure-void ratio relationships were slightly lower using seawater as compared to NaCl solution. However, the differences in the void ratios were only marginal. Similarly, the pressure-water contents relationship using NaCl solution was slightly higher than that of seawater at the same amount of vertical pressure applied. It was noted that, the plasticity and the compressibility characteristics of KB soil showed similar trend using both seawater and NaCl solution.